Modification of the Labbé Procedure. Issue 4 (June 2015) - Teven, Chad M.; Bank, Jonathan; Gottlieb, Lawrence J.; Reid, Russell R.
<x xml:space="preserve">Abstract</x> Abstract Modification of the lengthening temporalis myoplasty for reanimation of facial paralysis is presented. A patient experienced traumatic laceration of the left facial nerve resulting in left hemifacial paralysis. Multiple attempts at nerve repair were unsuccessful. For smile restoration, a Labbé procedure was performed. Because of inadequate length, the temporalis tendon could not be directly secured to the modiolus. Therefore, an inferiorly based temporalis fascia flap was recruited from the deep temporal fascia and reflected inferiorly to provide additional length by which the tendon could be secured to the modiolus. This technique provided immediate smile restoration and required no additional donor site.